FACTORS AFFECTING THE PURCHASE DECISION OF PEARL OYSTER SHELL CRAFTS IN AMBON CITY - Sipakoly, Selly (Dinasti International Journal of Digital Business Management, 2022)
This study aims to empirically examine the effect of price on purchasing decisions, the effect of product quality on purchasing decisions and the effect of promotional quality on purchasing decisions of pearl oyster shells in Batu Merah Village, Ambon City. This research is an empirical research, with the sampling technique used is purposive sampling. The analysis technique used is multiple linear regression analysis where the hypothesis test uses t-statistical test to test the partial regression coefficients and the F-statistical test to test the effect together or simultaneously with a confidence level of 0.05 or 5%. The test results show the price variable (X1) has a positive and significant influence on the purchasing decision variable. This is evidenced by the results of statistical tests which show a coefficient value of 0.570 with a significant value above 0.05. The product quality variable (X2) has a positive and significant influence on the purchasing decision variable. This is evidenced by the results of statistical tests which show the coefficient value of 0.132 with a significant value above 0.05 and the promotion quality variable (X3) has a positive and significant influence on the purchasing decision variable. This is evidenced by the results of statistical tests which show the coefficient value of 0.153 with a significant value above 0.05.